Comparison of non‐anthocyanin polyphenol accumulation in the berry skins of muscadine and European grapes during ripening in China. Issue 6 (13th November 2018) - Song, Shiren; Wei, Zheng; Huang, Yu; Guo, Wenfeng; Zhang, Yali; Yin, Ling; Qu, Junjie; Lu, Jiang
Abstract: The non‐anthocyanin polyphenol accumulation in the berry skins of muscadine grapes from South China during ripening was investigated, in comparison to European grapes, for two consecutive years, using ultra‐performance liquid chromatography tandem triple quadrupole time‐of‐flight mass spectrometry. A total of 121 components were tentatively identified, consisting of 48 ellagic acids and precursors (EP), 38 flavonols, 20 hydroxybenzoic acids, 6 hydroxycinnamic acids, 5 flavan‐3‐ols, and 4 stilbenes. EP (mostly ellagic acid derivatives) and flavonols (mainly isorhamnetin and quercetin derivatives) were, respectively, accumulated abundantly in the muscadine and European grape skins. Additionally, their variation had considerable differences during berry maturation. EP in muscadine cv. "Noble" skins showed a small decrease before veraison and a slight increase post‐veraison, yet the flavonols significantly increased as berry maturation in European skins, with a few exceptions. This is the interactional result between genotype and environmental factors, which obviously influences the polyphenol composition and concentration. Practical applications: Muscadine grapes, indigenous to the southeast of United States, have been introduced to South China in recent years. These grapes have unique polyphenol composition that differs from non‐muscadine grapes. Their polyphenol properties have been studied extensively in many but there are a few studies in our knowledge about the variation of these compounds at different berry developmental stages. This article evaluates the accumulation of non‐anthocyanin polyphenols in muscadine skins during berry maturation, in comparison to European grapes. The findings exhibit the polyphenol characteristics of these grapes cultivated in new locations across South China, and make further efforts to increase breeding quality and agronomic production, through improving preharvest treatments and agronomic performance during berry developmental stages, that lead to a high increase of polyphenol.